Stitching sustainability: local governments as mediators in hybrid environmental governance of mining-lake regions - Syam, Ridwan; Wisadirana, Darsono; Susilo, Edi; Nurhadi, Iwan; Latief, Muhammad Iqbal (Frontiers in Sustainability, 2026)
IntroductionLakes in mining regions face critical threats from environmental degradation and bureaucratic complexities spanning multiple levels of government. Despite this urgency, the role of local governments as intermediaries between central government regulations, mining corporate interests, and local community needs remains poorly understood. This study examines local government mediation roles in environmental governance at Lake Matano, East Luwu, Indonesia.MethodsThe research, conducted during July 2025, employed semi-structured interviews with eight key informants comprising government officials and community leaders, complemented by document analysis and participatory observation.ResultsThe findings reveal that environmental management authority remains fragmented across central, provincial, and district governments, creating jurisdictional overlap and weak coordination mechanisms. In response to this governance vacuum, local communities have developed autonomous management systems through grassroots initiatives. Local governments have demonstrated their capacity to serve as effective mediators, reconciling diverse stakeholder interests through trust-based persuasive approaches and dialogue rather than relying solely on formal regulatory enforcement. These findings introduce a novel conceptualization of local government as a “social weaver,” integrating formal legal frameworks with community acceptance and legitimacy.DiscussionThe study identifies three critical imperatives: strengthening inter-agency coordination mechanisms, formally recognizing local initiatives, and enhancing local government mediatory capacities. This research concludes that preserving lake ecosystems in mining regions requires more than regulatory reform alone. Success depends fundamentally on local governments’ ability to balance environmental protection, social justice, and economic interests within an integrated framework. The sustainability of these ecosystems ultimately hinges on developing governance approaches that harmonize competing demands while maintaining ecological integrity.